Efeito do extrato etanólico de Justicia secunda na esquistossomose mansônica experimental - Baptista, Bárbara (Universidade Federal de São Carlos, 2026)
Schistosomiasis mansoni is a socially determined parasitic disease caused by Schistosoma mansoni, whose morbidity is mainly associated with the granulomatous inflammatory response induced by parasite eggs retained in host tissues, particularly in the liver. Although praziquantel remains the only drug available for treatment, its limitations highlight the need to investigate new therapeutic strategies. In this context, natural products represent promising sources of bioactive compounds, including the ethanolic leaf extract of Justicia secunda, a species widely used in traditional medicine and reported to possess several biological activities. Therefore, this study aimed to evaluate the toxicity of the ethanolic leaf extract of J. secunda in NIH/3T3 murine fibroblasts and its effect on experimental S. mansoni infection in BALB/c mice. Cytotoxicity was assessed using the MTT assay, while nitric oxide production was determined by the Griess reaction. In the in vivo assay, forty mice were allocated into four groups: negative control, infected positive control, praziquantel-treated group, and J. secunda-treated group. Animals were infected with 80 S. mansoni cercariae, and treatments began on the 45th day post-infection. The evaluated parameters included fecal egg excretion using the Kato–Katz method, adult worm recovery by portal-hepatic and mesenteric perfusion, and liver histopathological alterations using hematoxylin and eosin (H&E) and Masson's trichrome staining. The extract exhibited low cytotoxicity at lower concentrations, whereas reduced cell metabolism and increased nitrite production were observed only at higher concentrations. In vivo, treatment with J. secunda did not significantly reduce fecal egg excretion or adult worm burden, indicating the absence of a marked anthelmintic effect at the tested dose. However, histopathological analysis suggested reduced apparent liver damage, characterized by better-defined granulomas and a more organized pattern of collagen deposition. In conclusion, the ethanolic leaf extract of J. secunda did not exhibit significant antischistosomal activity under the evaluated conditions but may have the potential to modulate liver alterations induced by S. mansoni infection. Further studies are required to quantify hepatic fibrosis, evaluate the immune response, and characterize the underlying mechanisms involved.
Effect of the ethanolic extract of Justicia secunda on experimental schistosomiasis mansoni
Keywords: Esquistossomose; Justicia secunda; Produtos Naturais; Fibrose; Inflamação; CIENCIAS BIOLOGICAS::PARASITOLOGIA; 3. Saúde e Bem-Estar